Integrating Generative AI and ChatGPT in Design Education: Impacts on Critical Thinking Development - Ouma, Brian Otieno; Mwangi, Eliud Kamau; Okoth, Adia Auma; Njeri, Achieng Wanjiru (International Journal of Graphic Design, 2025)
The integration of generative artificial intelligence (AI), and more particularly ChatGPT, into design education has brought about opportunities and challenges in developing critical thinking among students. As the design discipline increasingly intersects with emerging technologies, educators must take into account the implications of AI-powered tools on cultivating essential cognitive skills. The aim of this study is to investigate the implications of generative AI and ChatGPT on the critical thinking of design students in educational contexts. A mixed-methods approach was employed, combining quantitative data from pre- and post-intervention surveys with qualitative data from reflective diaries and focus group discussions. The subjects of the study were students majoring in visual communication design who utilized ChatGPT and generative AI tools throughout the semester. The findings attest to the improvement in critical thinking capability in problem definition, conceptualization, and self-reflection. In addition, the study affirmatively confirms that use of AI guided by others—additive to formal learning structures—may enable students' autonomy and creative thinking without reducing their creativity. These results suggest that generative AI, as an adjunct incorporated curriculally in strategic ways, could act as a pedagogical catalyst for advancing students' ability to think higher-order. This present study is part of the new debate concerning AI education in two essential ways: first, by means of a model of efficient application of generative AI by morals-based models. Research in the future will have to consider long-term effects and cross-disciplinary usage to further pedagogical strategies.